2018
DOI: 10.1177/1545968318799496
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Somatosensory Stimulation in Early Rehabilitation of Arm Paresis After Stroke: A Randomized Controlled Trial

Abstract: Background. Arm paresis is present in 48% to 77% of acute stroke patients. Complete functional recovery is reported in only 12% to 34%. Although the arm recovery is most pronounced during the first 4 weeks poststroke, few studies examined the effect of upper extremity interventions during this period. Objective. To investigate the effect of electrical somatosensory stimulation (ESS) delivered during early stroke rehabilitation on the recovery of arm functioning. Methods. A total of 102 patients with arm paresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Three of four studies in the acute and subacute periods [11,13,31] reported some significant differences in impairments (grip strength, hand function and sensation) to control participants but no changes in wider function of the upper-limb. The fourth study [10] undertaken in the acute period after stroke found no differences to control participants.…”
Section: Safetymentioning
confidence: 91%
See 3 more Smart Citations
“…Three of four studies in the acute and subacute periods [11,13,31] reported some significant differences in impairments (grip strength, hand function and sensation) to control participants but no changes in wider function of the upper-limb. The fourth study [10] undertaken in the acute period after stroke found no differences to control participants.…”
Section: Safetymentioning
confidence: 91%
“…Four studies were conducted in the chronic stage of stroke (Table 1) [22]. From the others, two were in the early subacute stage [11,31], a third was in the acute period after stroke [10] whilst another crossed two time periods (early subacute/late subacute) [13].…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…The ESS trial demonstrated no difference between the intervention and the control group (42), making it possible to merge the two cohorts for the purpose of the present study. Detailed information on the type and amount of delivered rehabilitation in the ESS trial is available elsewhere (42).…”
Section: Methodsmentioning
confidence: 99%